Longing for the lost (m)other – Postcolonial ambivalences in Arundhati Roy's The God of Small Things - Miriam Nandi (Journal of Postcolonial Writing, 2010)
Arundhati Roy’s novel The God of Small Things is frequently praised for its sensitivity to social injustice and its feminist politics, but it has also been criticized as exoticist and melodramatic. Thus, for instance, the representation of the lower class “subaltern” is essentially a fantasy, simultaneously unreachable and desirable, morally superior and physically perfect, a mythical “god of small things”, but also an object of terrible fear, mean and disgusting, driven by the lowest possible instincts. The present essay seeks to examine the various ways in which the political message carried by Roy’s novel is embedded in and undermined by a range of such fantasies, desires and fears.